2007
DOI: 10.1007/s00035-007-0804-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy and speciation in the orchid flora of the Iberian Peninsula

Abstract: Amich F., García-Barriuso M. and Bernardos S. 2007. Polyploidy and speciation in the orchid flora of the Iberian Peninsula. Bot. Helv. 117: 143 -157.The Iberian Peninsula, located at the western end of the Mediterranean Basin, is home to some 122 orchid species (1.5 % of the vascular plant flora). The high orchid species diversity, including 23 % of endemic species, suggests that there may be a high rate of polyploidy among Iberian orchids, given the overall importance of polyploidy in plant evolution. Chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
4
15
0
Order By: Relevance
“…(2010). In contrast with the species richness and the high diversity of floral characters, the homogeneous micromorphological pattern of testa cells found in Ophrys is also supportive of the recent radiation and rapid colonization proposed for the evolution of this genus along the Mediterranean basin (Soliva & al., 2001;Amich & al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(2010). In contrast with the species richness and the high diversity of floral characters, the homogeneous micromorphological pattern of testa cells found in Ophrys is also supportive of the recent radiation and rapid colonization proposed for the evolution of this genus along the Mediterranean basin (Soliva & al., 2001;Amich & al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One additional clade (tribe Malaxideae), present in central and northern Europe and represented by the genera Hammarbya, Liparis and Malaxis, does not reach the Iberian Peninsula. Amich et al (2007) indicated a total of 19 strictly endemic taxa for the Iberian Peninsula, an endemicity rate of approximately 16%. Of these taxa, 13 (68%) belong to the genera Epipactis and Ophrys; these narrow endemic orchid species show consistent ecological differences to their widespread congeners (Bernardos et al 2004b, unpubl.).…”
Section: Discussionmentioning
confidence: 99%
“…If larger territories are taken into account (e.g. the Ibero-French, Ibero-north-African or Ibero-French-north-African territories), the number of endemic taxa increases to 34 (27.88%) (Amich et al 2007). Thus, the Iberian orchid flora is relatively rich in endemisms at the species and subspecies level, but rather poor with respect to groups of higher rank.…”
Section: Discussionmentioning
confidence: 99%
“…Greilhuber and Ehrendorfer (1975) Cotrim et al (2009Cotrim et al ( , 2016 inferred that specimens from the western Iberian Peninsula with four alleles per individual for some microsatellite loci were tetraploid. Considering O. dyris, following an early report of tetraploid plants (Kullenberg 1961), Bernardos et al (2003), later cited by Aedo and Herrero (2005) and Amich et al (2007), reported counts of 2n = 4x =72 and 2n = 5x = 90. A confirmation of 2n = 4x =72 was reported by García-Barriuso et al (2010) for specimens from Montejunto region,…”
Section: Introductionmentioning
confidence: 99%